Extension of validity advance payment guarantee no. DBL/BAN/BG/376/2018 - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding extension of validity advance payment guarantee no. DBL/BAN/BG/376/2018 of BRAC University new campus project.